دور الريادة الاستراتيجية في تعزيز البراعة التسويقية: دراسة ميدانية على العاملين في شركة كرونجي للمشروبات الغازية - حمود، فوزي خلف حسين; مولوي، علام حسني (مركز السنبلة للبحوث والدراسات, 2023)
يهدف البحث إلى فهم مستوى البعد الريادي الاستراتيجي في شركة كرونجي والكشف عن مستوى القدرة التسويقية وعن مقدار التغيير على مستوى القدرة التسويقية نتيجة التغيرات في الريادي الاستراتيجي بالإضافة إلى فهم الفروقات الدالة إحصائيا في استجابات أفراد العينة للريادة الاستراتيجية وقدرات التسوق بناء على المتغيرات الديموغرافية. من أجل تحقيق أهداف البحث، استخدم الباحث الاستبيان كأداة لجمع البيانات وبلغ حجم عينة البحث من 230 موظفا من شركة كرونجي مستعينا بالمنهج الكمي والمنهج الاستنتاجي. وظهرت عدة استنتاجات منها إن الوسط الحسابي لجميع فقرات أبعاد الريادة الاستراتيجية في البراعة التسويقية (3.57%، 3.65%) بشكل متتالي. وهناك علاقة طردية ذات دلالة إحصائية بين أبعاد القيادة الاستراتيجية في البراعة التسويقية، وتظهر أن المتغيرات التي تؤثر على براعة التسويق هي: القيادة والإدارة الاستراتيجية. 65% من التغييرات في براعة التسويق ترجع إلى التغيير في الريادة الاستراتيجية. The research aims to understand the level of the strategic entrepreneurial dimension in Krongi Company and to reveal the level of marketing capacity and the amount of change in the level of marketing capacity as a result of changes in the strategic entrepreneur in addition to understanding the statistically significant differences in the responses of the sample members to strategic leadership and shopping capabilities based on demographic variables. In order to achieve the objectives of the research, the researcher used the questionnaire as a data collection tool and the research sample size of 230 employees from Krongi using the quantitative and deductive approaches. Several conclusions emerged, including that the arithmetic mean of all paragraphs of the dimensions of strategic leadership in marketing prowess (3.57%, 3.65%) respectively. There is a statistically significant positive relationship between the dimensions of strategic leadership in marketing prowess, and it appears that the variables that affect marketing prowess are: leadership and strategic management. 65% of changes in marketing prowess are due to a change in strategic leadership.
Keywords: ريادة الأعمال -- الإدارة الاستراتيجية -- القدرات التسويقية -- شركة كرونجي